Driving Factors Affecting Lecturers and Employees Performance During the Covid-19 Pandemic - Qristin violinda; Suwarno Widodo; Mahmud Yunus; Istiyaningsih Istiyaningsih; Rahmat Robi Waliyansyah (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2021)
The Covid-19 pandemic has enhanced business competition at both public and private universities. As a consequence, the competition encourages universities to promote a creative strategy. To deal with this issue, this study examines the driving factors affecting lecturers and employees at PGRI University Semarang during the Covid-19 Pandemic. The sample was selected using simple random sampling with a total of 206 respondents consisting of 81 employees and 125 lecturers. The measurement of the study adopted a Likert scale, and the data obtained were processed using Partial Least Square (PLS). The results of the study indicate that there is a direct influence of employee management on organizational culture. Additionally, this study remarks that a robust correlation between organizational learning and organizational culture as well as organizational culture can promote the performance of lecturers and employees. Lastly, there is no direct influence of employee arrangement on the performance of lecturers and employees. The largest total effect on the performance of lecturers and employees is organizational learning, which includes a direct effect of 39.3 percent and an indirect effect through the organizational culture of 21.9 percent. Keywords: Staffing Practices, Organizational Learning, organizational culture, employee performance